Electrolyte additive, electrolyte, secondary battery and electric equipment

By adding an electrolyte additive with a specific structure to the electrolyte to generate a CEI film, the problems of electrolyte oxidation and decomposition of the electrolyte and transition metal ions dissolution of the cathode material under high voltage are solved, and the circulation and storage performance of the battery are significantly improved.

CN119812463AActive Publication Date: 2025-04-11CHONGQING FUDI BATTERY RES INST CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311316470.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-11
Publication Date
2025-04-11
Estimated Expiration
2043-10-11

AI Technical Summary

Technical Problem

The existing electrolyte is prone to oxidation and decomposition at high voltages, resulting in battery inflation and capacity attenuation. The high voltage aggravates the dissolution of transition metal ions in the positive electrode material, damaging battery performance.

Method used

An electrolyte additive is provided, and its structure is shown in formula (I), which can preferentially oxidize and decompose during the charging and discharging of the battery, form a positive electrode electrolyte interface (CEI) film, stabilize the interface between the positive electrode sheet and the electrolyte, and inhibit side reactions and dissolution of transition metal ions.

Benefits of technology

Significantly extend the service life of the battery, improve the battery's room temperature and high-temperature circulation performance, improve the battery's high-temperature storage performance, reduce the battery's inflation risk, and improve the battery's safety performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812463A_ABST
    Figure CN119812463A_ABST
Patent Text Reader

Abstract

The invention provides an electrolyte additive, an electrolyte, a secondary battery and electric equipment, the structure of the electrolyte additive is as shown in formula (I): # imgabs0 #, x, y and n are respectively and independently natural numbers, and n is greater than or equal to 1; r1, R2 and R3 are respectively and independently selected from at least one of a hydrogen atom, a halogen atom, a substituted or unsubstituted alkyl group, a substituted or unsubstituted unsaturated alkyl group and a substituted or unsubstituted aryl group. The electrolyte additive is particularly suitable for an electrolyte for high working voltage, and the long cycle performance, the high-temperature cycle performance and the high-temperature storage performance of the battery under the high working voltage can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to electrolyte additives, electrolytes and secondary batteries, and electrical equipment. Background Art

[0002] With the advancement of technology, consumers have higher and higher requirements for the battery life of 3C electronic products and new energy vehicles, which requires the continuous improvement of battery energy density. Although the energy density of batteries can be improved by developing high-voltage positive electrode materials, the existing electrolyte is very prone to severe oxidation under high voltage, which leads to adverse consequences such as battery bloating. In addition, high voltage will aggravate the dissolution of transition metal ions in the positive electrode material, which will not only cause the collapse of the positive electrode material structure, but also cause the solid electrolyte film on the surface of the negative electrode to be destroyed, thereby causing a sharp decline in battery capacity. Summary of the invention

[0003] In view of this, the present application provides an electrolyte additive, an electrolyte and a secondary battery, and electrical equipment. The electrolyte additive is particularly suitable for an electrolyte for high operating voltage, and can improve the long cycle performance, high temperature cycle performance, and high temperature storage performance of the battery at high operating voltage.

[0004] In a first aspect, the present application provides an electrolyte additive, the structure of which is shown in formula (I):

[0005]

[0006] Wherein, x, y and n are each independently a natural number, and n≥1; and R1, R2, and R3 are each independently selected from at least one of a hydrogen atom, a halogen atom, a substituted or unsubstituted alkyl group, a substituted or unsubstituted unsaturated hydrocarbon group, and a substituted or unsubstituted aryl group.

[0007] The above-mentioned electrolyte additives can be preferentially oxidized and decomposed during the battery charging and discharging process, and form a cathode electrolyte interface (cathode-electrolyte interface, CEI) film on the surface of the positive electrode plate, thereby stabilizing the interface between the positive electrode plate and the electrolyte, inhibiting side reactions of the electrolyte, and inhibiting the dissolution of transition metal elements in the positive electrode material under high voltage. At the same time, it greatly reduces the interface impedance, improves the battery's room temperature and high temperature cycle performance, enhances the battery's high temperature storage performance, and significantly extends the battery's service life.

[0008] Optionally, 1≤n≤3.

[0009] Optionally, 0≤x≤5; 0≤y≤5.

[0010] Optionally, the substituted or unsubstituted alkyl group has 1 to 5 carbon atoms; the substituted or unsubstituted unsaturated hydrocarbon group has 2 to 5 carbon atoms; and the substituted or unsubstituted aryl group has 6 to 10 carbon atoms.

[0011] Optionally, the substituents in the substituted alkyl group and the substituted unsaturated hydrocarbon group are each independently selected from at least one of a halogen atom, a cyano group, a carboxyl group and a sulfonic acid group; the substituents in the substituted aromatic group are selected from at least one of a halogen atom, a cyano group, a carboxyl group, a sulfonic acid group and an alkyl group.

[0012] Optionally, the substituents in the substituted alkyl group, the substituted unsaturated hydrocarbon group and the substituted aryl group are each independently selected from halogen atoms.

[0013] In a second aspect, an embodiment of the present application provides an electrolyte, comprising an organic solvent, an electrolyte salt, and at least one electrolyte additive as shown in formula (I):

[0014]

[0015] Wherein, x, y and n are each independently a natural number, and n≥1; and R1, R2, and R3 are each independently selected from at least one of a hydrogen atom, a halogen atom, a substituted or unsubstituted alkyl group, a substituted or unsubstituted unsaturated hydrocarbon group, and a substituted or unsubstituted aryl group.

[0016] The above electrolyte additives can be used to improve the high voltage resistance of the electrolyte, thereby improving the long cycle performance, high temperature cycle performance and high temperature storage performance of the battery at high operating voltage.

[0017] Optionally, based on the total weight of the electrolyte, the mass percentage of the electrolyte additive is 0.1%-20%.

[0018] Optionally, the electrolyte further includes a negative electrode film-forming agent; based on the total weight of the electrolyte, the mass percentage of the negative electrode film-forming agent is 0.1%-15%.

[0019] The third aspect of the present application provides a secondary battery, comprising a positive electrode, a negative electrode and an electrolyte; wherein the electrolyte comprises the electrolyte additive provided in the first aspect of the present application.

[0020] Due to the use of the electrolyte additive provided in the embodiments of the present application, the battery can have good long cycle performance, high temperature cycle performance and high / low temperature storage performance at a higher operating voltage.

[0021] The fourth aspect of the present application provides an electrical device, including the secondary battery provided by the third aspect of the present application. DETAILED DESCRIPTION

[0022] At present, in order to meet consumers' demand for the battery life of electronic devices, the industry often improves the energy density of batteries by developing positive electrode materials with high working voltage. However, the existing electrolyte system cannot match the above high voltage battery system. Taking lithium batteries as an example, when the battery voltage is higher than 4.2V (vs Li / Li + ), the side reaction between the electrolyte and the positive electrode material will intensify, and the electrolyte will easily undergo oxidative decomposition and produce gas, leading to adverse consequences such as rapid consumption of the electrolyte, battery swelling, battery capacity decay, and even safety hazards.

[0023] In order to solve the above problems, the present application provides an electrolyte additive in an embodiment, and the structure of the electrolyte additive is shown in formula (I):

[0024]

[0025] Wherein, x, y and n are each independently a natural number, and n≥1; and R1, R2, and R3 are each independently selected from at least one of a hydrogen atom, a halogen atom, a substituted or unsubstituted alkyl group, a substituted or unsubstituted unsaturated hydrocarbon group, and a substituted or unsubstituted aryl group.

[0026] The above-mentioned dicyanocyclic lactone electrolyte additive has both cyano and cyclic lactone structures. The oxidation potential of the cyclic lactone structure is relatively low, which allows the electrolyte additive to preferentially oxidize other components in the electrolyte during the charge and discharge process of the secondary battery, and form a dense and uniform (cathode-electrolyte interface, CEI) film on the surface of the positive electrode plate. The above-mentioned CEI film can effectively inhibit the side reaction between the electrolyte and the positive electrode material, thereby effectively inhibiting the oxidation of the electrolyte, greatly reducing the risk of battery flatulence, and improving the safety performance of the battery; at the same time, the synergistic effect of the cyano and cyclic lactone structures can further modify the interface of the above-mentioned CEI film, so as to further improve the interface stability of the positive electrode plate / electrolyte, long-term inhibit the growth of the positive electrode film layer impedance and the electrochemical charge transfer impedance during the cycle, and significantly improve the room temperature and high temperature cycle performance of the battery. In addition, the two cyano groups in the electrolyte additive can also complex the transition metal ions in the positive electrode material (for example, high-nickel ternary positive electrode material, etc.) to form a relatively stable ring structure, which can effectively inhibit the dissolution of transition metal ions in the positive electrode material under high voltage, thereby improving the problem of structural collapse of the positive electrode material, and significantly reducing the risk of transition metal ions migrating to the negative electrode surface to damage the solid electrolyte membrane, further improving the high-voltage resistance of the battery. At the same time, the above-mentioned substances with cyano groups can adsorb H2O and fluorine-containing substances such as HF that may be generated during the battery cycle, and form amide substances, reducing the high-temperature flatulence caused by the decomposition of electrolyte solvents catalyzed by fluorine-containing substances such as HF, and further improving the high-temperature cycle and high-temperature storage performance of the battery under high-voltage conditions.

[0027] In some embodiments of the present application, 1≤n≤3. Exemplarily, the value of n can be 1, 2, or 3. In this way, the steric hindrance of the electrolyte additive can be controlled within a more appropriate range, so that it can maintain a high surface reactivity and can give full play to its effect during the first charge and discharge of the battery and subsequent cycles. At the same time, it is also beneficial to control the viscosity of the final electrolyte within a more appropriate range, facilitate the wetting of the electrolyte on the electrode, and ensure that the ionic conductivity of the electrolyte is high, thereby facilitating the rate performance of the battery.

[0028] In some embodiments of the present application, 0≤x≤5. Exemplarily, the value of x can be 0, 1, 2, 3, 4, 5. In this way, the viscosity of the final electrolyte is controlled within a suitable range, so that the ionic conductivity of the electrolyte is controlled to be higher and the wetting performance is better; and the steric hindrance of the electrolyte additive is also reduced, so that it can smoothly form a CEI film on the surface of the positive electrode sheet, and can effectively inhibit the dissolution of the positive transition metal ions.

[0029] In some implementations of the present application, 0≤y≤5. For example, the value of y can be 0, 1, 2, 3, 4, 5. Controlling the value of y within the above range can achieve the same principle and effect as controlling the value of x, which will not be repeated here.

[0030] In some specific embodiments, the electrolyte additive satisfies 1≤n≤3, 0≤x≤5 and 0≤y≤5 at the same time.

[0031] In some embodiments of the present application, the substituted or unsubstituted alkyl group has 1 to 5 carbon atoms; the substituted or unsubstituted unsaturated hydrocarbon group has 2 to 5 carbon atoms; the substituted or unsubstituted aryl group has 6 to 10 carbon atoms. That is, R1, R2, and R3 in the electrolyte additive are each independently selected from hydrogen atoms, halogen atoms, substituted or unsubstituted C 1~5 Alkyl, substituted or unsubstituted C 2~5 Unsaturated hydrocarbon, substituted or unsubstituted C 6~10 At least one of the aromatic groups. Limiting the carbon number of the hydrocarbon group or aromatic group to a certain range is conducive to maintaining the viscosity of the electrolyte additive within an appropriate range to ensure the wetting performance and ion conductivity of the electrolyte. For example, the carbon number of the substituted or unsubstituted alkyl group can be 1, 2, 3, 4, or 5; the unsubstituted C 1~5 The alkyl group may be any one of methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl, tert-butyl, n-pentyl, neopentyl, n-hexyl, cyclopropyl or cyclobutyl. The number of carbon atoms in the substituted or unsubstituted unsaturated hydrocarbon group may be 2, 3, 4, 5, etc.; wherein the unsubstituted C 2~5The unsaturated hydrocarbon group may be an alkenyl group, such as any one of vinyl, propenyl and butenyl, etc.; or an alkynyl group, such as any one of ethynyl and propynyl, etc.; the number of carbon atoms of the substituted or unsubstituted aryl group may be 6, 7, 8, 9, 10; wherein the unsubstituted aryl group may be phenyl, naphthyl, etc. In some specific embodiments, the hydrogen atoms in the aryl group are replaced by alkyl groups, which are referred to as "alkylaryl" for convenience of description. The hydrogen atoms in the alkylaryl group (including hydrogen atoms in the alkyl group and hydrogen atoms on the aromatic ring) may also be further replaced by other groups. In this case, the number of carbon atoms in the substituted or unsubstituted alkylaryl group is controlled to be 7 to 10. For example, the number of carbon atoms in the substituted or unsubstituted alkylaryl group is 7, 8, 9, 10; wherein the above-mentioned alkylaryl group may be benzyl, phenethyl, etc.

[0032] In some specific embodiments of the present application, at least one of R1, R2, and R3 in the electrolyte additive is an alkyl aryl group, which is more beneficial to the high temperature performance of the battery.

[0033] In some embodiments of the present application, the substituents in the substituted alkyl and the substituted unsaturated hydrocarbon groups are independently selected from at least one of halogen atoms, cyano groups, carboxyl groups and sulfonic acid groups; the substituents in the substituted aryl groups are selected from at least one of halogen atoms, cyano groups, carboxyl groups and sulfonic acid groups. It can be understood that in some specific embodiments, the hydrogen atoms in the aryl group are replaced by alkyl groups, or the hydrogen atoms in the alkyl group are replaced by aryl groups; that is, R1, R2, and R3 can also be substituted or unsubstituted alkaryl groups independently, or, each independently, substituted or unsubstituted aralkyl groups; at this time, the hydrogen atoms in the alkaryl or aralkyl group can be further replaced by at least one of halogen atoms, cyano groups, carboxyl groups and sulfonic acid groups. Exemplarily, the substituted alkaryl group can be a halogenated benzyl group, etc. In some specific embodiments, the above substituents are independently selected from halogen atoms. The halogen atoms can include fluorine atoms (F), chlorine atoms (Cl), bromine atoms (Br), and iodine atoms (I). The presence of halogen atoms in the CEI membrane can also effectively improve its structural stability, thus helping to further improve the cycle stability of the battery; at the same time, the local strong polarity of the halogenated end groups can increase the ionic conductivity of the electrolyte, helping to improve the rate performance of the battery, for example, helping the battery to achieve fast charging performance.

[0034] In some specific embodiments of the present application, the substituted C 1~5 Alkyl, substituted C 2~5 Unsaturated hydrocarbon, substituted C 6~10 Aryl, substituted C 7~10 The substituents in the alkylaryl group are each independently selected from at least one of a halogen atom, a cyano group, a carboxyl group and a sulfonic acid group.

[0035] The present application also provides an electrolyte solution, including an organic solvent, an electrolyte salt, and at least one electrolyte solution additive as shown in formula (I):

[0036]

[0037] Wherein, x, y and n are each independently a natural number, and n≥1; and R1, R2, and R3 are each independently selected from at least one of a hydrogen atom, a halogen atom, a substituted or unsubstituted alkyl group, a substituted or unsubstituted unsaturated hydrocarbon group, and a substituted or unsubstituted aryl group.

[0038] The electrolyte contains an electrolyte additive having a structure as shown in formula (I). During the charge and discharge process of the battery, part of the electrolyte additive can undergo an oxidation reaction in priority to other components in the electrolyte (e.g., organic solvent), thereby forming a dense and relatively uniform CEI film on the surface of the positive electrode, thereby improving the interface between the positive electrode and the electrolyte, for example, effectively inhibiting the side reaction between the electrolyte and the positive electrode material, thereby alleviating the consumption of the electrolyte and the generation of gas, and reducing the expansion rate of the battery cell; at the same time, the cyanide group in the electrolyte additive (mainly the undecomposed electrolyte additive) can also inhibit the dissolution of transition metal ions in the positive electrode material (e.g., ternary positive electrode material), absorb free water molecules in the battery and HF molecules that may be generated during the cycle, so the electrolyte can improve the safety performance and long cycle performance of the battery, especially the long cycle performance, high temperature cycle performance, high temperature storage performance and safety performance of the battery under high voltage. The detailed working principle of the electrolyte additive can be found in the description of the electrolyte additive above, which will not be repeated here.

[0039] In some embodiments of the present application, 1≤n≤3. For example, the value of n can be 1, 2, or 3. In some embodiments of the present application, 0≤x≤5. For example, the value of x can be 0, 1, 2, 3, 4, or 5. In some embodiments of the present application, 0≤y≤5. For example, the value of y can be 0, 1, 2, 3, 4, or 5. The effects that can be achieved by controlling the values ​​of x, y, and n to be within the above ranges have been described above and will not be repeated here.

[0040] In some specific embodiments, in the electrolyte, the electrolyte additives satisfy 1≤n≤3, 0≤x≤5 and 0≤y≤5. In this case, the viscosity of the electrolyte is more conducive to the transmission of active ions.

[0041] In some embodiments of the present application, R1, R2, and R3 in the electrolyte additive are independently selected from hydrogen atoms, halogen atoms, substituted or unsubstituted C 1~5 Alkyl, substituted or unsubstituted C 2~5 Unsaturated hydrocarbon, substituted or unsubstituted C 6~10At least one of the aromatic groups. Limiting the carbon number of the above hydrocarbon group or aromatic group to a certain range is conducive to maintaining the viscosity of the electrolyte additive within an appropriate range to ensure the wetting performance and ion conductivity of the electrolyte. Exemplarily, the carbon number of the substituted or unsubstituted alkyl group can be 1, 2, 3, 4, 5; the carbon number of the substituted or unsubstituted unsaturated hydrocarbon group can be 2, 3, 4, 5, etc.; the carbon number of the substituted or unsubstituted aromatic group can be 6, 7, 8, 9, 10. Similarly, the above R1, R2, and R3 can also be independently substituted or unsubstituted C 7~10 Alkyl aryl, substituted or unsubstituted C 7~10 As for the arylalkyl group, reference may be made to the above description and will not be repeated here.

[0042] In some embodiments of the present application, similarly, the substituents in the substituted alkyl, substituted unsaturated hydrocarbon, substituted aryl, substituted arylalkyl and substituted alkylaryl are each independently selected from at least one of a halogen atom, a cyano group, a carboxyl group and a sulfonic acid group. 1~5 Alkyl, substituted C 2~5 Unsaturated hydrocarbon, substituted C 6~10 Aryl and substituted C 7~10 The substituents in the alkylaryl group are each independently selected from at least one of a halogen atom, a cyano group, a carboxyl group and a sulfonic acid group. In some specific embodiments, the substituents are each independently selected from a halogen atom. Among them, the halogen atom may include a fluorine atom (F), a chlorine atom (Cl), a bromine atom (Br), and an iodine atom (I). The local strong polar halogenated end group can increase the ionic conductivity of the electrolyte, which is beneficial to improve the rate performance of the battery, for example, it is beneficial for the battery to achieve fast charging performance.

[0043] In some specific embodiments of the present application, at least one of R1, R2, and R3 in the electrolyte additive is a C 7~10 Alkyl aryl. This is more conducive to the high temperature performance of the battery.

[0044] In some embodiments of the present application, the electrolyte contains at least one electrolyte additive represented by the following formula (A) to formula (F):

[0045]

[0046]

[0047] In some embodiments of the present application, the mass percentage of the electrolyte additive is 0.1%-20% based on the total weight of the electrolyte. For example, the mass percentage of the electrolyte additive in the electrolyte can be 0.1%, 0.2%, 0.5%, 1%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 8%, 10%, 12%, 15%, 18%, 20%, etc. In some specific embodiments of the present application, the mass percentage of the above-mentioned electrolyte additive in the electrolyte can be in the range of 0.5% to 5%. A portion of the electrolyte additives can be used to form the CEI film, and a portion of the electrolyte additives will still be free in the electrolyte. Therefore, an appropriate amount of electrolyte additives can not only generate a complete and moderately thick CEI film on the surface of the positive electrode, but can also effectively reduce the problem of the thick CEI film affecting the battery performance; it also greatly reduces the risk of excessive free electrolyte additives squeezing out the share of other essential substances in the electrolyte, leading to deterioration of battery performance.

[0048] In some embodiments of the present application, the electrolyte further includes a negative electrode film-forming agent. The negative electrode film-forming agent can form a stable solid electrolyte interface (SEI) film on the surface of the negative electrode during the battery charging and discharging process, thereby improving the interface of the negative electrode / electrolyte, which is beneficial to further improve the cycle performance, storage performance and safety performance of the battery.

[0049] In some embodiments of the present application, the mass percentage of the negative electrode film-forming agent is 0.1%-15% based on the total weight of the electrolyte. Exemplarily, the mass percentage of the negative electrode film-forming agent in the electrolyte can be 0.1%, 0.2%, 0.5%, 1%, 2%, 5%, 8%, 10%, 12%, 15%, etc. In some specific embodiments, the mass percentage of the negative electrode film-forming agent in the electrolyte is 1% to 5%. Controlling the content of the negative electrode film-forming agent within the above range can not only generate a complete SEI film with a suitable thickness on the surface of the negative electrode, but also will not squeeze out the content of other necessary substances in the electrolyte, which is conducive to the normal performance of the battery.

[0050] In some embodiments of the present application, the above-mentioned negative electrode film-forming agent can be selected from substances well known to those skilled in the art. Exemplarily, the negative electrode film-forming agent is one or more of vinyl carbonate, fluoroethylene carbonate, vinyl ethylene carbonate, 1,3-propane sultone, 1,3-propylene sultone, vinyl sulfate, lithium difluorophosphate, lithium difluorobisoxalate phosphate, and lithium tetrafluorooxalate phosphate. In some specific embodiments, the above-mentioned negative electrode film-forming agent is selected from one or more of vinyl sulfate, lithium difluorooxalate borate, lithium difluorobisoxalate phosphate, and lithium tetrafluorooxalate phosphate. In this way, the negative electrode film-forming agent and the electrolyte additive also have a certain synergistic effect, which is conducive to further improving the comprehensive electrochemical performance of the battery. In some embodiments of the present application, the organic solvent in the electrolyte includes but is not limited to one or more of ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, γ-butyrolactone, methyl formate, ethyl acetate, methyl acetate, propyl acetate, butyl acetate, ethyl propionate, propyl propionate and butyl propionate.

[0051] In some embodiments of the present application, the electrolyte salt may be a material known to those skilled in the art, specifically a lithium salt. The above-mentioned lithium salt includes but is not limited to one or more of lithium hexafluorophosphate, lithium perchlorate, lithium tetrafluoroborate, lithium bis(trifluoromethylsulfonyl)imide and lithium bis(fluorosulfonyl)imide salts. In the present application, there is no special requirement for the content of the electrolyte salt in the electrolyte, and its content can be referred to the conventional amount used in the art.

[0052] The present application also provides a secondary battery, including a positive electrode, a negative electrode and an electrolyte provided in the present application. Due to the use of the electrolyte provided in the present application, the battery can have good long cycle performance, high temperature cycle performance and high temperature storage performance at a higher operating voltage.

[0053] In some specific embodiments of the present application, the secondary battery is a lithium-ion battery.

[0054] In some embodiments of the present application, the positive electrode includes a positive electrode current collector and a positive electrode active material layer disposed on at least one side of the positive electrode current collector. According to different secondary battery systems, the material of the above-mentioned positive electrode current collector is selected from any well-known material in the field that is adapted to a specific secondary battery system. The positive electrode active material includes a material that can achieve reversible extraction / embedding of active ions (for example, lithium ions, sodium ions, potassium ions, magnesium ions, zinc ions, aluminum ions, etc.). Taking lithium-ion batteries as an example, the positive electrode active material can be, but is not limited to, lithium cobalt oxide (LiCoO2), lithium iron phosphate (LiFePO4), LiNi 0.33 Co 0.33 Mn 0.33 O2(NCM111), LiNi 0.4 Co 0.2Mn 0.4 O2(NCM424),LiNi 0.5 Co 0.2 Mn 0.3 O2(NCM523),LiNi 0.6 Co 0.2 Mn 0.2 O2(NCM622),LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811) or more.

[0055] In some embodiments of the present application, the positive electrode active material includes a high-nickel ternary material, and the high-nickel ternary material includes a ternary nickel-cobalt-manganese material, which can be LiNi 0.33 Co 0.33 Mn 0.33 O2(NCM111), LiNi 0.4 Co 0.2 Mn 0.4 O2(NCM424),LiNi 0.5 Co 0.2 Mn 0.3 O2(NCM523),LiNi 0.6 Co 0.2 Mn 0.2 O2(NCM622),LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM811),LiNi 0.85 Co 0.075 Mn 0.075 O. High nickel ternary materials have high specific capacity and can greatly improve the energy density of batteries.

[0056] In the present application, the negative electrode of the secondary battery may be any negative electrode known in the art.

[0057] In the present application, a separator is further sandwiched between the positive electrode and the negative electrode. The separator can be any separator known to those skilled in the art.

[0058] The embodiments of the present application also provide an electrical device, including the electrical device provided in the embodiments of the present application.

[0059] In some implementations of the present application, the above-mentioned electrical equipment includes but is not limited to 3C electronic products, power vehicles, etc.

[0060] The technical solution of the present application is further illustrated by multiple embodiments below.

[0061] Example 1

[0062] (1) Preparation of electrolyte: Ethylene carbonate (EC) and ethyl methyl carbonate (EMC) are mixed in a mass ratio of 3:7, and then an electrolyte additive as shown in formula (A), a negative electrode film-forming agent (specifically vinylene carbonate, VC) and an electrolyte salt (specifically lithium hexafluorophosphate, LiPF6) are added to the above mixture until the molar concentration of the electrolyte salt is 1.0 mol / L, the mass percentage of the electrolyte additive is 1%, and the mass percentage of the negative electrode film-forming agent is 2%.

[0063] (2) preparing a positive electrode sheet, the preparation method of which is as follows: mixing a ternary positive electrode material (specifically NCM622), Super-P (conductive agent), CNT (conductive agent) and a binder (specifically polyvinylidene fluoride, PVDF) in a mass ratio of 96:1.5:1:1.5, and then dispersing them in a solvent (specifically N-methylpyrrolidone, NMP), stirring the above mixture in a vacuum mixer until it is stable and uniform to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on both sides of an aluminum foil with a thickness of 18 μm, and after drying at room temperature, transferred to a 120°C forced air oven for drying for 2 hours, and then subjected to cold pressing and slitting processes to obtain a positive electrode sheet.

[0064] (3) A negative electrode sheet is prepared by the following preparation method: artificial graphite, Super-P, a binder (specifically styrene-butadiene rubber, SBR) and a thickener (specifically sodium carboxymethyl cellulose, CMC) are mixed in a mass ratio of 95.6:1.4:1:2, and then dispersed in a solvent (specifically deionized water) to obtain a negative electrode slurry, and the negative electrode slurry is evenly coated on both sides of a copper foil with a thickness of 8 μm, and after drying at room temperature, the slurry is transferred to a 120° C. forced air oven for drying for 2 h, and then subjected to cold pressing and slitting processes to obtain a negative electrode sheet.

[0065] (4) The assembly and formation of the battery, the steps are as follows: in an argon glove box with a water content of less than 5ppm, the positive electrode plate, the diaphragm and the negative electrode plate are stacked in order to obtain a bare battery cell, the bare battery cell is loaded into a battery shell and welded, and then 1.6g of the above electrolyte is injected into the battery shell, and the battery shell is sealed to prepare a lithium-ion battery. The above battery is first charged to 1.5V with a current of 40mA (0.05C) and maintained at 1.5V for 10h to fully wet the battery electrode sheet. After the constant voltage is completed, the battery is initially charged with a smaller current of 8mA (C / 100) for 10h to form a stable and dense SEI film, and then charged to 4.35V with a current of 40mA (0.05C), and then discharged to 3.0V. The secondary battery of Example 1 is obtained.

[0066] Example 2-Example 16

[0067] On the basis of Example 1, some parameters of the electrolyte and the components of the electrolyte additives in Example 1 are replaced. For the convenience of description, the parameters or substances changed in Examples 2 to 16 relative to Example 1 are summarized in Table 1.

[0068] In order to highlight the beneficial effects of the embodiments of the present application, comparative examples 1-3 are provided.

[0069] The parameters or substances changed in Comparative Examples 1-3 and Example 1 relative to Example 1 are also summarized in Table 1.

[0070] Table 1

[0071]

[0072]

[0073] In Table 1, the structural formula of the electrolyte additive in each embodiment is as follows:

[0074]

[0075]

[0076] Electrochemical performance test

[0077] (1) Normal temperature cycle test

[0078] The secondary batteries prepared in the above embodiments and comparative examples were charged to 4.4V at 1C constant current at 25°C, then charged to a cut-off current of 0.05C at constant voltage, left to stand for 30 minutes, and then discharged to 2.5V at 1C constant current, which was recorded as one charge and discharge cycle. The above conditions were cycled for 1000 cycles; wherein, the capacity retention rate (%) of the secondary battery after 1000 cycles = (discharge capacity of the 1000th cycle / discharge capacity of the first cycle) × 100%. The test results are summarized in Table 2.

[0079] (2) High temperature cycle performance test

[0080] The lithium ion batteries prepared in the above embodiments and comparative examples were charged to 4.4V at 1C constant current at 45°C, then charged to a cut-off current of 0.05C at constant voltage, left to stand for 30 minutes, and then discharged to 2.5V at 1C constant current, which was recorded as one charge and discharge cycle. The batteries were then cycled for 500 cycles under the above conditions; wherein, the capacity retention rate (%) of the secondary battery after 500 cycles = (discharge capacity of the 500th cycle / discharge capacity of the first cycle) × 100%; the test results are summarized in Table 2.

[0081] (3) High temperature storage performance test

[0082] The secondary batteries prepared in the above embodiments and comparative examples were charged to 4.4V at 1C constant current and constant voltage at 25°C, cut off at 0.05C, and left standing for 30 minutes, and then discharged to 2.5V at 1C constant current, and the discharge capacity was calculated as the initial capacity C0, and the battery volume V0 before storage was measured, and the battery was transferred to a high-temperature test cabinet and stored at 55°C for 14 days; after the storage was completed, the test battery was taken out, left at room temperature for 24 hours, and the battery volume V1 after storage was measured, and then discharged to 2.5V at 1C constant current, and the discharge capacity C1 was recorded, and left standing for 120 minutes, and charged to 4.4V at 1C constant current and constant voltage, cut off at 0.05C, and left standing for 30 minutes. After that, the battery was discharged to 2.5V at 1C constant current, and the discharge capacity C2 was recorded;

[0083] Capacity remaining rate (%) = C1 / C0 × 100%;

[0084] Capacity recovery rate (%) = C2 / C0×100%;

[0085] Battery volume expansion rate (%) = [(V1-V0) / V0]×100%; the test results are summarized in Table 2.

[0086] Table 2

[0087]

[0088] Combining the parameters in Table 1 and the data in Table 2, when the electrolyte of each secondary battery contains a negative electrode film-forming agent and an additive (the electrolyte additive of the embodiment or the adiponitrile of comparative example 3) (Examples 1-14 and Comparative Examples 1-3), the room temperature, high temperature cycle performance and high temperature storage performance of the embodiment battery are significantly higher than those of the comparative example battery.

[0089] In particular, it can be seen from the data of Examples 1-16 that when the electrolyte provided by the present application is used (that is, containing both the negative electrode film-forming agent and the electrolyte additive provided by the present application), it is more conducive to the normal temperature / high temperature cycle performance and high temperature storage performance of the battery. It can be seen from the data of Example 7 and Example 8 that when the negative electrode film-forming agent is selected from further preferred substances such as vinyl sulfate, it is more conducive to the performance of the battery.

[0090] By comparing the data of Examples 1-6, it can be found that when the content of the electrolyte additive in the electrolyte is within the range recommended in this application (Examples 2-6), it is more conducive to the battery performance; when the content of the electrolyte additive is within the range further recommended in this application (Examples 3-5), the battery's cycle performance and high-temperature storage performance can be further improved.

[0091] The above is an exemplary embodiment of the present application. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made thereto without departing from the principles of the present application. These improvements and modifications are also considered to be within the scope of protection of the present application.

Claims

1. An electrolyte additive, characterized in that: The structure of the electrolyte additive is shown in formula (I): Wherein, x, y and n are each independently a natural number, and n≥1; R1, R2, R3 are each independently selected from at least one of a hydrogen atom, a halogen atom, a substituted or unsubstituted alkyl group, a substituted or unsubstituted unsaturated hydrocarbon group and a substituted or unsubstituted aryl group.

2. The electrolyte additive according to claim 1, characterized in that: 1≤n≤3。 3. The electrolyte additive according to claim 1, characterized in that: 0≤x≤5;0≤y≤5.

4. The electrolyte additive according to claim 1, characterized in that: The substituted or unsubstituted alkyl group has 1 to 5 carbon atoms; the substituted or unsubstituted unsaturated hydrocarbon group has 2 to 5 carbon atoms; and the substituted or unsubstituted aryl group has 6 to 10 carbon atoms.

5. The electrolyte additive according to claim 1 or 4, characterized in that: The substituents in the substituted alkyl group and the substituted unsaturated hydrocarbon group are each independently selected from at least one of a halogen atom, a cyano group, a carboxyl group and a sulfonic acid group; the substituents in the substituted aryl group are selected from at least one of a halogen atom, a cyano group, a carboxyl group, a sulfonic acid group and an alkyl group.

6. The electrolyte additive according to claim 5, characterized in that: The substituents in the substituted alkyl group, the substituted unsaturated hydrocarbon group and the substituted aryl group are each independently selected from halogen atoms.

7. An electrolyte, characterized in that: The electrolyte comprises at least one electrolyte additive according to any one of claims 1 to 6, an organic solvent and an electrolyte salt.

8. The electrolyte according to claim 7, characterized in that Based on the total weight of the electrolyte, the mass percentage of the electrolyte additive is 0.1%-20%.

9. The electrolyte according to claim 7 or 8, characterized in that The electrolyte also includes a negative electrode film-forming agent; based on the total weight of the electrolyte, the mass percentage of the negative electrode film-forming agent is 0.1%-15%.

10. A secondary battery, characterized in that: The secondary battery comprises a positive electrode, a negative electrode and an electrolyte; wherein the electrolyte comprises the electrolyte additive according to any one of claims 1 to 6.

11. An electrical device, characterized in that: The electric device comprises the secondary battery as claimed in claim 10.

Citation Information

Patent Citations

  • Non-aqueous organic electrolyte, lithium ion secondary battery containing non-aqueous organic electrolyte, preparation method of lithium ion secondary battery and terminal communication equipment

    CN102522590A

  • High-voltage electrolyte and lithium ion battery containing same

    CN111092264A

  • Non-aqueous electrolyte solution for lithium secondary battery and lithium secondary battery comprising same

    CN115461905A

  • High-voltage lithium cobalt oxide lithium ion battery electrolyte and lithium ion battery

    CN116742118A

  • Electrochemical element and driving electrolyte therefor

    JP1995283083A